2015
DOI: 10.1016/j.molmet.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte SIRT1 knockout promotes PPARγ activity, adipogenesis and insulin sensitivity in chronic-HFD and obesity

Abstract: ObjectiveAdipose tissue is the primary site for lipid deposition that protects the organisms in cases of nutrient excess during obesogenic diets. The histone deacetylase Sirtuin 1 (SIRT1) inhibits adipocyte differentiation by targeting the transcription factor peroxisome proliferator activated-receptor gamma (PPARγ).MethodsTo assess the specific role of SIRT1 in adipocytes, we generated Sirt1 adipocyte-specific knockout mice (ATKO) driven by aP2 promoter onto C57BL/6 background. Sirt1flx/flxaP2Cre+ (ATKO) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(117 citation statements)
references
References 83 publications
5
111
0
1
Order By: Relevance
“…Given previous findings suggesting that hyperacetylation of PPARγ at lysines 293 also leads to an increase in Ser273 phosphorylation (Qiang et al, 2012), it is likely that NAMPT-mediated NAD + biosynthesis and SIRT1 together regulate PPARγ Ser273 phosphorylation by modulating CDK5 phosphorylation and PPARγ acetylation. Consistent with this idea, adipocyte-specific Sirt1 knockout mice have increased acetylation and Ser273 phosphorylation of PPARγ in adipose tissue (Mayoral et al, 2015). In addition, several independent groups have reported that adipocyte-specific Sirt1 knockdown/knockout is causatively related to adipose tissue dysfunction and systemic metabolic complications (Chalkiadaki and Guarente, 2012; Gillum et al, 2011; Mayoral et al, 2015).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Given previous findings suggesting that hyperacetylation of PPARγ at lysines 293 also leads to an increase in Ser273 phosphorylation (Qiang et al, 2012), it is likely that NAMPT-mediated NAD + biosynthesis and SIRT1 together regulate PPARγ Ser273 phosphorylation by modulating CDK5 phosphorylation and PPARγ acetylation. Consistent with this idea, adipocyte-specific Sirt1 knockout mice have increased acetylation and Ser273 phosphorylation of PPARγ in adipose tissue (Mayoral et al, 2015). In addition, several independent groups have reported that adipocyte-specific Sirt1 knockdown/knockout is causatively related to adipose tissue dysfunction and systemic metabolic complications (Chalkiadaki and Guarente, 2012; Gillum et al, 2011; Mayoral et al, 2015).…”
Section: Discussionmentioning
confidence: 80%
“…Consistent with this idea, adipocyte-specific Sirt1 knockout mice have increased acetylation and Ser273 phosphorylation of PPARγ in adipose tissue (Mayoral et al, 2015). In addition, several independent groups have reported that adipocyte-specific Sirt1 knockdown/knockout is causatively related to adipose tissue dysfunction and systemic metabolic complications (Chalkiadaki and Guarente, 2012; Gillum et al, 2011; Mayoral et al, 2015). Nonetheless, we cannot exclude the possibility that other sirtuins and NAD + -consuming enzymes, such as poly(ADP-ribose) polymerases (Belenky et al, 2007; Canto et al, 2015; Imai and Yoshino, 2013), also mediate effects induced by the defects in NAPMPT-mediated NAD + biosynthesis in ANKO mice.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In 3T3-L1 adipocytes genetic or pharmacological Sirt1 inhibition increased the expression of inflammatory cytokines upon tumor necrosis factor 1 alpha stimulation, whereas Sirt1 activation had the opposite effect [133]. In agreement, genetic or antisense oligonucleotide mediated Sirt1 deficiency in rodents leads to elevated inflammation characterized by increased macrophage infiltration and mRNA expression of inflammatory cytokines in WAT under normal [107] and HFD conditions [101], [115], [117], [134]. However, during long-term HFD adipocyte specific Sirt1 deletion reduced WAT inflammation in contrast to the other findings [115].…”
Section: Sirts and Parps In Adipose Tissue Function In Basal And Obesmentioning
confidence: 83%
“…Sirt 1 is involved in food intake regulation [47,48], gluconeogenesis in the liver [49], fat mobilization from white adipose tissue, cholesterol metabolism, and energy metabolism [50,51]. In adipose tissue, Sirt 1 activates fat mobilization by inhibiting peroxisome proliferator-activated receptor gamma (PPAR-gamma) [52,53] and in the pancreas Sirt 1 repression decreases insulin secretion with effects on beta cell uncoupling protein 2 levels [54]. Sirt 1 influences mitochondrial biogenesis in the adipose tissue and liver with relevance to NAFLD [10].…”
Section: Defective Adipose Tissue-liver Crosstalk In the Induction Ofmentioning
confidence: 99%